Eladio Dieste - Pedreschi, Remo (Thomas Telford, 2000)
This volume reviews the work of Eladio Dieste. It discusses Dieste's own approach to his work, using many examples, and explores the interrelationship between the structural form and architecture of the buildings.
Keywords: Dieste, Eladio, -- 1917-2000 -- Criticism and interpretation.; Architecture, Modern -- 20th century.; Architecture -- Uruguay -- History -- 20th century.; Structural engineering -- Uruguay.; elektronické knihy; electronic books